Empowering older adults through age- and eco-friendly principles: the AFECO project and the Portuguese experience - Bello, Paola; Saavedra, Ines; Dantas, Carina; Machado, Natália; van Staalduinen, Willeke (Magyar Gerontológia, 2024)
Europe's demography has significantly changed in the last decade with older adults (defined here as those aged 65 years or more) in the EU-27, rising from 90.5 million at the start of 2019 to reach 129.8 million by 2050. The ageing population is driving significant transformations in culture, institutions, and communities.